The reduction of noxious emissions using urea based on Selective Non-Catalytic Reduction in small scale bio fuel combustion system - Mohamad Shaiful Ashrul, Ishak; Mohammad Nazri, Mohd. Jaafar (Canadian Center of Science and Education, 2011)
Link to publisher's homepage at http://ccsenet.org/